BOOK REVIEW: ENGLISH CURRICULUM AND MATERIAL DEVELOPMENT - Vega, Nofvia De; Atmowardoyo, Haryanto (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Book reviews are intended to inform and evaluate a book's content and quality. It presents review critiques of the English curriculum and material development book by Pryla Rochmawati. The reviewer classified into four major sections from 11 chapters: curriculum and syllabus, curriculum components, the English curriculum in Indonesia, and the development of English-language materials. To begin, curriculum and syllabus are introduced briefly in language and explained in simple terms like those found in the first paragraph. Secondly, the curriculum is addressed by analyzing the needs of the students, establishing objectives, assessing their progress, and evaluating their progress. The third section discusses the Indonesian curriculum and how it has evolved. Material development based on Tomlinson's theory is presented in the fourth section. An evaluation of the author's visual approach and the content will be conducted in the review.